Fatty acid transduction of nitric oxide signaling. Nitrolinoleic acid is a hydrophobically stabilized nitric oxide donor - Schopfer, Francisco J; Baker, Paul R S; Giles, Gregory; Chumley, Phil; Batthyany, Carlos; Crawford, Jack; Patel, Rakesh P; Hogg, Neil; Branchaud, Bruce P; Lancaster, Jr, Jack R; Freeman, Bruce A (The Journal of biological chemistry, 2005)
The aqueous decay and concomitant release of nitric oxide (*NO) by nitrolinoleic acid (10-nitro-9,12-octadecadienoic acid and 12-nitro-9,12-octadecadienoic acid; LNO2) are reported. Mass spectrometric analysis of reaction products supports a modified Nef reaction as the mechanism accounting for the generation of *NO by the aqueous reactions of fatty acid nitroalkene derivatives. Nitrolinoleic acid is stabilized by an aprotic milieu, with LNO2 decay and *NO release strongly inhibited by phosphatidylcholine/cholesterol liposome membranes and detergents when present at levels above their critical micellar concentrations. The release of *NO from LNO2 was induced by UV photolysis and triiodide-based ozone chemiluminescence reactions currently used to quantify putative protein nitrosothiol and N-nitrosamine derivatives. This reactivity of LNO2 complicates the qualitative and quantitative analysis of biological oxides of nitrogen when applying UV photolysis and triiodide-based analytical systems to biological preparations typically abundant in nitrated fatty acids. The results reveal that nitroalkene derivatives of linoleic acid are pluripotent signaling mediators that act not only via receptor-dependent mechanisms, but also by transducing the signaling actions of *NO via pathways subject to regulation by the relative distribution of LNO2 to hydrophobic versus aqueous microenvironments.